Study of Metanil Yellow Toxic Effect on The Pregnant Mice (Mus musculus) strain Balb/C During Fetal Organogenesis Development - Setyawati, Arie; Rahmawati, Rita Rizky; Hariri, Muhammad Rifqi; Tenzer, Amy (Proceeding International Conference on Global Resource Conservation, 2013)
The aim of this research is to identify the toxic effect of metanil yellow in pregnant mice during fetal organogenesis development. Twenty five pregnant mice at 2,5 months age were gavaged during 7th-16th day of gestation in five doses treatment groups per day at: 1) 0 mg per 20 g body weight, 2) 0,435 mg per 20 g body weight, 3) 0,87 mg per 20 g body weight, 4) 1,305 mg per 20 g body weight, and 5) 1,74 mg per 20 g body weight. Everyday, the weight of female mice were measured and on the 18th day, fetuses were taken by caesarean section to observe the fetal development. The observation was about maternalâs reproductive performance, body weight and liver, kidney, and spleen morphology. Data was analysed descriptively. The result reveals that all doses affect the maternalâs body weight, caused liver, kidney and spleen inflammation and also caused fetal abortion.Keywords: fetal organogenesis development, metanil yellow, pregnant mice Balb/C, toxic effectÂ